DO GENERATIONAL MEMBERSHIP AND PSYCHOGRAPHIC CHARACTERISTICS INFLUENCE POSITIVE WORD OF MOUTH IN A UNIVERSITY CONTEXT? - Ann Mitsis; Patrick Foley (Asian Academy of Management Journal, 2012)
The specific question that this paper seeks to answer is: do psychographic culturally-anchored values act as antecedents to positive word of mouth intention independently of an individual's generational (Generation Y rather than Generation X) membership? This question has important implications for service-based industries like universities. Results suggest that positive word of mouth intention is influenced by psychographic characteristics. Generation Y's positive word of mouth antecedents were: high collectivism, high uncertainty avoidance, and high power distance. Generation X's had only one antecedent, high collectivism. This paper concludes by outlining the areas for future research of Generation Y and the implication of this research for university leaders tasked with enhancing positive word of mouth in current students and alumni.